Performance stability of photovoltaic modules in different climates. (30th June 2017) - Schweiger, Markus; Bonilla, Johanna; Herrmann, Werner; Gerber, Andreas; Rau, Uwe
Abstract: The current–voltage( I‐V) characteristics of 15 different photovoltaic modules are monitored during more than 2 years of operation at four locations (Germany, Italy, India and Arizona) corresponding to four different climate zones. The electrical stability of the photovoltaic modules during the time of outdoor exposure is investigated in terms of measured I‐V curve translated to standard test conditions. This translation compensates the influence of module temperature, irradiance, spectral effects and soiling on the I‐V curves. The changes of output power after these corrections are attributed to initial consolidation phases, to long‐term degradation of the electrical properties and to seasonal cycles associated with metastabilities. Modules made from crystalline Si turn out to show no or only minor effects. Thin‐Film modules (CdTe, Cu(In, Ga)Se2 and thin‐film Si) exhibit a wide spread of metastable behaviour with consistent patterns for identical modules in different climates but with significant differences amongst different manufacturers of the same thin‐film technology. We show further that this metastable behaviour influences the energy yield of the modules. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The metastable behaviour and long‐term stability of various photovoltaic module technologies was investigated systematically in different climates by a new approach based on internationally approved standards. Relative changes in the power performance at standard test conditions could be traced, using outdoor I‐V curve data, with an uncertainty of ±1% independent of meteorological influences. The metastable behaviour of thin‐film photovoltaic modules is a decisive factor significantly influencing their energy yield especially during the first year of outdoor exposure.